KOMUNIKASI POLITIK DAN DIPLOMASI BERBASIS KEARIFAN LOKAL DALAM MASA KAMPANYE PEMILUKADA KABUPATEN KUANTAN SINGINGI TAHUN 2011 - Ridwan, Mumammad (Nakhoda: Jurnal Ilmu Pemerintahan, 2013)
Political communication is important and feels more important when we listen to and browse thefunctions of political communication itself , especially when political communication and politicaldiplomacy based on local wisdom . Political communication is done to promote the politicaldesires of Regents candidates Singingi Kuantan , poor judgment in taking the values of localwisdom which contains many morals , truth values , family values and religious values can not beblocked causing conflicts terjaddi The Regency Kuantan Singingi Election in 2011 . One exampleof local wisdom kuantan singing the " Batobo " which contains the value of cooperation , harmony, harmony and familial characteristics ( mutual aid ) . Still feels less and less done well to beused and exploited in political campaign strategy in the General Election in Kuantan districtSingingi .Keywords : Communication Politics , Diplomacy , Local Wisdom , Campaign , Election , RegencyKuantan Singingi